High-Throughput Sequencing Reveals the Loss-of-Function Mutations in GALT Cause Recessive Classical Galactosemia - Li, Lulu; Ma, Li; Sun, Min; Jiao, Jiancheng; Zhang, Yudong; Tang, Yue; Yang, Nan; Kong, Yuanyuan (Frontiers in Pediatrics, 2020)
Background: Classical Galactosemia (CG) is a rare autosomal recessive metabolic disease caused by mutations in the galactose-1-phosphate uridyl transferase (GALT) gene. This study aim to identify pathogenic mutations underlying classic galactosemia in two Chinese families. Methods: We collected two Chinese families blood and extracted genomic DNA. High-throughput sequencing , sanger sequencing and bioinformatics analysis were used to investigate the molecular cause of manifestations in two Chinese families.Result: We found a novel compound heterozygous mutations (c.396C>G; p.His132Gln and c.974C>T; p.Pro325Leu) in family 1 and a homozygous missense variant(c.974C>T; p.Pro325Leu) in family 2. Bioinformatics and Sanger sequencing was performed to verify the identified variants.Conclusion: The present study identified the GALT mutations as a genetic etiology in two Chinese families with classic galactosemia, which expands the phenotypic and mutational spectrum of GALT. Our findings could be useful in providing evidence for prenatal interventions and more precise pharmacological treatments to patients. High-throughput sequencing conducted in our study is a convenient and useful tool for clinical diagnosis of galactosemia and other associated genetic disorders.